Decarbonisation and intergovernmental fiscal relations Policy challenges and reform options - de Mello, Luiz (OECD Publishing, 2023)
This paper explores the nexus between decarbonisation and intergovernmental fiscal relations, focusing on related challenges and reform options. It highlights the significant role of subnational governments in tackling climate change. Subnational and national governments share responsibilities in areas such as taxation, spending and regulation pertaining to environmental protection, as well as climate change mitigation and adaptation, which calls for effective intergovernmental co-operation to align policy objectives and implementation strategies. The paper outlines decarbonisation requirements across sectors and discusses subnational government involvement in service delivery, investment, revenue generation and regulatory frameworks. Policy options to strengthen subnational contributions to national decarbonisation goals are presented. While focusing primarily on OECD countries, the paper acknowledges the need for improved information on subnational decarbonisation efforts in both advanced and developing countries
Keywords: Environment; Taxation; Development